Methods of increasing herbage yield and seed productivity of Echinacea purpurea under conditions of Krasnodar krai - R. R. Thaganov; N. I. Sidelnikov; O. L. Saibel (Овощи России)
Relevance. For the production of pharmaceutical products from raw materials of Echinacea purpurea L., it is necessary to have a sufficient amount of high-quality seeds when planting production areas with high yields of aboveground mass.Methods. On Echinacea purpurea of the second year of vegetation in order to increase herbage yield and seed productivity, tests of organomineral fertilizer EcoFus (1.5 l/ha) with microfertilizers (Siliplant (0.5 l/ha) or Cytovit (1.0 l/ha). As a standard, we used double foliar feeding with Siliplant (0.5 l/ha). The above-ground mass was mowed in the third ten days of August. On seed plantations we tested: in the early growth phase EcoFus (1.5 l/ha), in the stemming phase – growth regulators Epin-extra (0.06 l/ha), Agat-25K (0.04 l/ha) and their tank mixtures. Seed collection was carried out in mid-September.Results. Double spraying with complex – EcoFus with microfertilizers, promoted activation of growth processes, and it resulted in 22-26% increase of above-ground mass yield, 5-7% increase of phenylpropanoids in it, their collection per hectare increased within 28-35%. A more effective complex was revealed: EcoFus (1.5 l/ha) with Siliplant (0.5 l/ha), which allowed to increase yield and collection of active substances by 26 and 35% in comparison with the control, and in comparison with the reference (Siliplant 0.5 l/ha) – by 11 and 15%, respectively. In order to increase seed productivity of Echinacea purpurea, spraying with EcoFus at the beginning of vegetation of plants and EcoFus complex with bioregulators Agat and Epin-extra in the phase of stemming was applied. Foliar fertilization with these tank mixtures resulted in earlier flowering of plants (by 2-4 days), increased the number of inflorescences by 9-10%, inflorescences with seeds by 14-15% and seed weight of one inflorescence by 12- 14%. Activation of generative processes of Echinacea purpurea had a positive effect on seed yield and their quality: yield increased by 21-25%, weight of 1000 pieces by 7-8% and their germination by 2-3%.